Pelaksanaan Perjanjian Kerjasama Pemanfaatan Aset Daerah Melalui Bangun Guna Serah (Build Operate And Transfer) Antara Pemerintah Daerah Provinsi NTB Dengan Pihak Swasta Dalam Pembangunan Dan Pengelolaan Nusa Tenggara Barat - Sahruddin; Wagian, Diangsa; Fathoni, M. Yazid (Jurnal Risalah Kenotariatan, 2024)
The purpose of this research is to determine the implementation of the Build Operate and Transfer cooperation agreement between the NTB Regional Government and PT. Lombok Plaza in the construction and management of the West Nusa Tenggara Convention Center. To find out the obstacles in implementing the Build Operate and Transfer cooperation agreement between the NTB Regional Government and PT. Lombok Plaza in the construction and management of the West Nusa Tenggara Convention Center. Academically, this research is expected to be useful in enriching the development of thoughts and concepts related to the law on procurement of goods and services, especially those related to self-managed procurement of goods/services in villages. Practically, it is hoped that the results of this research will be able to contribute ideas to the government and the community, especially village budget managers and users. Cooperation Agreement Between Regional Government and PT. Lombok Plaza in the construction of the West Nusa Tenggara Convention Center occurred in 2016 where the parties agreed to build a representative facility and infrastructure as a place for meetings, exhibitions/promotions as well as a place to hold national, regional and international events using the Build system. Use of Handover (BGS). Where the MOU (Momerendum of Understanding) regarding the construction of the West Nusa Tenggara Convention Center contains an agreement regarding the stages, procedures, construction period, contribution and exclusive rights that must be paid by PT. Lombok Plaza both during the preparation period and during the management period, and there is also rights and obligations of each party, and regulates the termination of the agreement, sanctions and methods for resolving problems. The Regional Government immediately takes a firm stance to terminate the cooperation agreement with PT Lombok Plaza To continue the development of the West Nusa Tenggara Convention Center and its supporting facilities, the Regional Government will immediately look for other investors by entering into a new cooperation agreement.